Urban ecology in a developing world: why advanced socioecological theory needs Africa. Issue 10 (30th August 2013) - McHale, Melissa R; Bunn, David N; Pickett, Steward TA; Twine, Wayne
Abstract : Socioecological theory, developed through the study of urban environments, has recently led to a proliferation of research focusing on comparative analyses of cities. This research emphasis has been concentrated in the more developed countries of the Northern Hemisphere (often referred to as the "Global North"), yet urbanization is now occurring mostly in the developing world, with the fastest rates of growth in sub‐Saharan Africa. Countries like South Africa are experiencing a variety of land‐cover changes that may challenge current assumptions about the differences between urban and rural environments and about the connectivity of these dynamic socioecological systems. Furthermore, questions concerning ecosystem services, landscape preferences, and conservation – when analyzed through rural livelihood frameworks – may provide insights into the social and ecological resilience of human settlements. Increasing research on urban development processes occurring in Africa, and on patterns of kinship and migration in the less developed countries of the "Global South", will advance a more comprehensive worldview of how future urbanization will influence the progress of sustainable societies.